Cultural interaction between the capitals of Tlemcen and Fess (Muwahidi covenant) (مجلة إحالات, 2026)
This study includes research into the cultural acculturation in the cities of the Islamic West. We studyin particular the cities of Tlemcen and Fess in the Muwahidi covenant, by identifying the reasons thatcontributed to activating this intellectual and cultural movement. And its role to forming the Maghreb mindin the past, and It comes at the forefront of these reasons: The scientific journey that scientists have chosen as an approach to increase. It was migration to the major scientific capitals, Added to that politicalmotivations, that has long been ravaged the Islamic west and it has disturbed the purity of their Scientifics in their assemblies. They were forced to leave their cities.The give and take was the result of this forcedmigration. Therefore, this study strives to show the cultural interaction between the Scientifics of Tlemcenand Fess.